2012
DOI: 10.1093/jnci/djs481
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Risk in Cystic Fibrosis: A 20-Year Nationwide Study From the United States

Abstract: The overall burden of cancer in CF patients remains low; however they have an increased risk of digestive tract cancer, particularly following transplantation. They also have increased risk of lymphoid leukemia and testicular cancer, and decreased risk of melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
245
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(286 citation statements)
references
References 20 publications
16
245
2
5
Order By: Relevance
“…62,63 The fact that elevated expression of the Mirc1/Mir17-92 cluster is associated with several types of malignancies, and our findings that this cluster is elevated in CF patients, raises growing concerns about cancer predispositions in the CF population. 29,64,65 Current strides in research aim to prolong and improve the life of CF patients, however CF patients are prone to different types of cancers later in life.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…62,63 The fact that elevated expression of the Mirc1/Mir17-92 cluster is associated with several types of malignancies, and our findings that this cluster is elevated in CF patients, raises growing concerns about cancer predispositions in the CF population. 29,64,65 Current strides in research aim to prolong and improve the life of CF patients, however CF patients are prone to different types of cancers later in life.…”
Section: Discussionmentioning
confidence: 89%
“…29,64,65 Current strides in research aim to prolong and improve the life of CF patients, however CF patients are prone to different types of cancers later in life. 62,65,66 Elevated expression of the Mirc1/ Mir17-92 cluster in CF may contribute to this predisposition. It has also been shown that the Mirc1/Mir17-92 cluster is highly expressed in intestinal tissue in CF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other less well-defined but emerging complications may well become common in the future care for adults living into their fourth decade and beyond. Gastro-intestinal cancers are more common in adults with CF, with the most prevalent being colorectal cancers [17,18]. The metabolic consequences of being overweight or obese with CF are unclear; however, as adults live longer and potentiator and corrector therapy increases body mass index, problems with obesity may become an issue [19].…”
Section: Complexity Of Adult Cf Carementioning
confidence: 99%
“…The study by Maisonneuve et al (2) was based on data from the US Cystic Fibrosis Foundation (CFF) Patient Registry for the period from 1990 to 2009, which is representative of the whole CF population, and includes approximately 85% of patients receiving care at one of the 120 CFF-accredited care centers in the United States. Due to confidentiality issues and the switch to medical electronic records, cancer case ascertainment was, however, incomplete for the period from 2000 to 2009.…”
Section: Risk Of Colorectal Cancer After Solid Organ Transplantationmentioning
confidence: 99%